2012
DOI: 10.1038/nchem.1244
|View full text |Cite
|
Sign up to set email alerts
|

Taking Ockham's razor to enzyme dynamics and catalysis

Abstract: The role of protein dynamics in enzyme catalysis is a matter of intense current debate. Enzyme-catalysed reactions that involve significant quantum tunnelling can give rise to experimental kinetic isotope effects with complex temperature dependences, and it has been suggested that standard statistical rate theories, such as transition-state theory, are inadequate for their explanation. Here we introduce aspects of transition-state theory relevant to the study of enzyme reactivity, taking cues from chemical kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
271
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 236 publications
(278 citation statements)
references
References 80 publications
7
271
0
Order By: Relevance
“…Several of these proposals suggest that the anomalous temperature and pressure dependences of experimentally observed reaction rates and kinetic isotope effects are the consequence of protein motions on the pico-to femtosecond timescale that reduce the width and/ or height of the potential energy barrier along the chemical reaction coordinate. However, a connection between promoting motions and potential energy barrier modulation has never been demonstrated directly, and recent work has shown that the temperature dependence of kinetic isotope effects can be accounted for by conformational effects for a number of enzymes (5). Whereas some authors postulate dynamics as a key driving force in catalysis (1)(2)(3)(4), others have performed analyses showing activation free-energy reduction, which is an equilibrium property, to be the source of catalysis (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Several of these proposals suggest that the anomalous temperature and pressure dependences of experimentally observed reaction rates and kinetic isotope effects are the consequence of protein motions on the pico-to femtosecond timescale that reduce the width and/ or height of the potential energy barrier along the chemical reaction coordinate. However, a connection between promoting motions and potential energy barrier modulation has never been demonstrated directly, and recent work has shown that the temperature dependence of kinetic isotope effects can be accounted for by conformational effects for a number of enzymes (5). Whereas some authors postulate dynamics as a key driving force in catalysis (1)(2)(3)(4), others have performed analyses showing activation free-energy reduction, which is an equilibrium property, to be the source of catalysis (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In conclusion, while we agree that it is reasonable to use Ockham's razor to exclude the dynamical proposal, 183 however, we also believe that basically using the "inductive" approach of showing that the proposal does not work for any current test case (as we have done here) is the best way to establish that enzyme catalysis is not due to dynamical effects.…”
Section: Discussionmentioning
confidence: 95%
“…The manner in which it is plotted suggests analogy with the concept of an energy landscape, which has become a fundamental idea guiding how chemists and physicists think about both kinetics and dynamics in a range of chemical systems, from small molecules to complex materials and biochemical systems. 52,53 An energy landscape is effectively a topological map of a system's potential energy, V, at a range of different congurations. Within any localized region of the energy landscape, the gradient of the energy, dV/dq, relates the topology of the energy landscape to the classical forces felt by a particular molecular conguration.…”
Section: Depth Images and Energy Landscapesmentioning
confidence: 99%